Honest thief [videorecording (DVD)] - Williams, Mark (Director); Williams, Mark (Director); Neeson, Liam; Walsh, Kate, 1967-; Courtney, Jai (Universal Pictures Home Entertainment, 2020)
When a bank robber decides to turn himself in to start over with a woman he loves, he is double-crossed by two ruthless FBI agents.